The Meaning of Gendhing Kodhok Ngorek in the Panggih Procession of a Traditional Javanese Wedding Ceremony - Suyoto Suyoto; Aris Setiawan (Journal of Urban Society's Arts, 2023)
This article aims to understand the meaning of Gending Kodok Ngorek, as the music that accompanies wedding rituals (Panggih) in Java. The data were collected through observation, a literature review, and interviews. The problem was addressed using Clifford Geertz’s cultural interpretive concept, which argues that cultural facts exist in the mind (as knowledge), are manifested in models, and determine behaviour and action in life, and Yasraf Amir Pilliang’s semiotics of culture, which describes how meaning is formed through media and signs. The research concludes that the panggih ceremony, a procession in which the bride and bridegroom come together, can be interpreted philosophically, socially, and symbolically. Based on the musical pitches used, philosophically understood as a marker of a husband and wife who are making love. Its masculine character is manifested in the panunggul alit pitch (1), which symbolizes a male frog, while its feminine character is manifested in pitch nem (6), which symbolizes a female frog. Etymologically, Kodhok Ngorek means singing frog, of course in the water. Water is understood as a symbol of fertility, as a sign of the hope that the husband and wife will soon be blessed with offspring. Makna Gendhing Kodhok Ngorek Dalam Prosesi Panggih Upacara Pernikahan Adat Jawa. Artikel ini bertujuan untuk memahami Gending Kodok Ngorek sebagai musik pengiring upacara pernikahan (Panggih) di Jawa. Pengumpulan data dilakukan melalui observasi, studi literatur, dan wawancara. Masalah tersebut dianalisis dengan menggunakan konsep interpretasi budaya Clifford Geertz, yang berpendapat bahwa fakta budaya ada dalam pikiran (sebagai pengetahuan), diwujudkan dalam model, dan menentukan perilaku dan tindakan dalam kehidupan, dan semiotika budaya Yasraf Amir Pilliang, yang menggambarkan bagaimana makna dibentuk melalui media dan tanda. Hasil penelitian menunjukkan bahwa upacara panggih, sebuah prosesi di mana kedua mempelai bertemu, dapat dimaknai secara filosofis, sosial, dan simbolis. Berdasarkan nada musik yang digunakan, secara filosofis dipahami sebagai penanda kedua sejoli yang sedang bercinta. Sifat maskulinnya diwujudkan dalam nada panunggul alit (1) yang melambangkan katak jantan, sedangkan sifat femininnya diwujudkan dalam nada nem (6) yang melambangkan katak betina. Secara etimologi Kodhok Ngorèk berarti katak bernyanyi, sudah barang tentu di dalam air. Air dipahami sebagai simbol kesuburan, sebagai penanda harapan agar pasangan sejoli segera dikaruniai keturunan.